2019
DOI: 10.1016/j.dib.2019.104461
|View full text |Cite
|
Sign up to set email alerts
|

Data on the effects of Glochidion zeylanicum leaf extracts in Caenorhabditis elegans

Abstract: The present article contains the data on the effects of Glochidion zeylanicum leaf extracts in C. elegans, which is related to the article " Glochidion zeylanicum leaf extracts exhibit lifespan extending and oxidative stress resistance properties in Caenorhabditis elegans via DAF-16/FoxO and SKN-1/Nrf-2 signaling pathways" Chatrawee et al., 2019. This dataset was generated to better understand the antioxidant and anti-aging properties of G. zeylanicum leaf extracts in C. elegans. The bioactive compounds of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(35 citation statements)
references
References 3 publications
0
35
0
Order By: Relevance
“…Several studies have reported that polyphenols, including gallic acid [ 32 , 34 ], catechin [ 13 , 40 , 41 ] and quercetin [ 33 , 42 , 43 ], promote neurite outgrowth activity. The presence of phenolic compounds as well as gallic acid, catechin, and quercetin in GZM extract may be responsible for the observed behavior ( Supplementary Figure S1 ) [ 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies have reported that polyphenols, including gallic acid [ 32 , 34 ], catechin [ 13 , 40 , 41 ] and quercetin [ 33 , 42 , 43 ], promote neurite outgrowth activity. The presence of phenolic compounds as well as gallic acid, catechin, and quercetin in GZM extract may be responsible for the observed behavior ( Supplementary Figure S1 ) [ 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that phenolic antioxidants can protect against neurotoxicity induced by glutamate, Aβ peptides, and oxidative stress, which mainly depends on Nrf2/ARE signaling pathways [ 13 , 17 , 49 , 50 , 51 , 52 ]. GZM extract contains phenolic compounds including gallic acid, catechin, and quercetin ( Supplementary Figure S1 ) [ 11 , 12 ]. Thus, neuroprotective effects mediated by the SIRT1/Nrf2 signaling pathway may result from the presence of bioactive compounds in the GZM extract.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…from Simeulue, Aceh, Indonesia. G. zeylanicum is known to have potential as anti-tumor, anti-cancer, antioxidant and anti-aging agents (Duangjan et al, 2019;Sharma et al, 2011;Tanaka et al, 2004). Meanwhile, U. cordata has anti-hyperglycemic and antimicrobe antivities (Abdullah, 2016;Syafriana et al, 2021).…”
Section: Introductionmentioning
confidence: 99%